Impact of root observation windows on plant performance, root development, and rhizosphere-microbial communities during late vegetative growth of field-grown winter wheat - Loreen Sommermann; Jan Helge Behr; Narges Moradtalab; Saskia Windisch; Soumitra Paul Chowdhury; Michael Rothballer; Ingo Schellenberg; Doreen Babin; Kornelia Smalla; Lorrie Maccario; SØren J. SØrensen; Uwe Ludewig; et al. (Plant and Soil, 2026)
Background and Aims Root observation windows (RW) installed in the field provide a tool for non-destructive monitoring of root development and rhizosphere processes. However, the highly invasive installation process, which requires cutting soil profiles, may affect plant development and, ultimately, the outcome of the experiments. This study systematically compares plant development with and without the installation of RW. Methods Using the location of a long-term field experiment, the responses of winter wheat to different intensities of tillage, N-fertilization, and use of fungicides were compared for plants grown along root windows and in undisturbed control plots. Sampling was performed during late vegetative growth, six weeks after RW installation, with comparisons of shoot and root biomass, root length, mineral nutritional status, stress-related gene expression, stress metabolites, and the composition of microbial communities reflecting rhizosphere (RH) conditions. Results The presence of RW did not significantly affect most of the parameters analyzed. As an exception, RW plants showed increased foliar concentrations of several nutrients (K, Mg, Ca, Cu, Mn), potentially attributable to reduced inter-plant competition because RW were installed along border rows of the experimental plots. By contrast, N-fertilization intensity and fungicide use affected plant biomass, root growth, and fungal communities. Tillage intensity primarily affected fine-root production, the composition of RH-microbial communities, and physiological stress indicators in leaf tissue. Conclusion The results suggest only a limited influence on performance of winter wheat six weeks after RW installation under the selected experimental conditions, with plant responses and experimental results comparable to undisturbed controls.

Towards urban climate justice: Integrating social vulnerability in climate adaptation planning - Saskia Neumann; Julie M.L. Berta; Thomas Elliot; Lars Bodum (Environmental Development, 2026)

Histamine H1- and H4-receptor expression in human colon-derived cell lines - Jasper Carsten Schrammel; Martin König; Miriam Frommer; Kaya Saskia Andersen; Marla Kirsten; Roland Seifert; Detlef Neumann; Bastian Schirmer (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
In previous studies, we demonstrated the involvement of H 4 R in inflammatory bowel disease (IBD) and IBD-associated colon cancer in mice and could ascribe H 4 R-mediated histamine function to colon epithelial cells. The transferability of obtained data to humans is however lacking. Functional expression of H 4 R on colon epithelial cells is a prerequisite to pursue the hypothesis of involvement of H 4 R in carcinogenesis. Thus, we here compared the expression of histamine receptor subtypes in a series of cell lines. Out of these, three colon-derived cell lines displaying different combinations of H 1 R and H 4 R expression were submitted to functional analyses. Human hematopoietic HMC-1, HL-60, and U937, lung-derived A549 and Calu-3, and colorectal LoVo, SW 480, Caco-2, HT-29, and HCT116 cells were included in the study. mRNA expression was quantified by RT-qPCR. For functional analyses, Caco-2, HT-29, and HCT116 cells were treated by incubation with 1 – 10 µM histamine in the presence or absence of selective histamine receptor antagonists. Calcium mobilization, cAMP accumulation, and cell proliferation were measured by fluorimetry, mass spectrometry, and real-time bioimpedance measurements, respectively. Histamine receptor expression was heterogeneous in the cell lines tested. In most cell lines, we detected H 1 R mRNA while H 4 R mRNAs were found only occasionally. The colon-derived epithelial cell lines LoVo, SW480, and HT-29 expressed H 1 R mRNA exclusively, while in HCT116 cells H 1 R and H 4 R mRNAs and in CaCo-2 H 2 R mRNA were detectable. Subsequent functional analyses in HT29, Caco-2, and HCT116 cells, however, indicated that only HT-29 responded to histamine stimulation, by means of H 1 R. For a detailed analysis of histamine receptor function, esp. that of H 1 R and H 4 R, in human colon-derived cell lines, the cell lines tested here are not fully convenient unless genetically modified.